2019
DOI: 10.1177/0268355519835618
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-directed thrombolysis vs. anticoagulation for the prevention and treatment of post-thrombotic syndrome in deep vein thrombosis: An updated systematic review and meta-analysis of randomized trials

Abstract: Background Oral anticoagulation therapy was the mainstay of deep vein thrombosis treatment but recently, catheter-directed thrombolysis has emerged as an alternative. Objective To compare the efficacy and safety of the two strategies. Methods Medline, Embase and Cochrane CENTRAL were reviewed. Outcomes of interest included post-thrombotic syndrome, thromboembolic events, mortality, bleeding risk and iliofemoral patency. A random effects model meta-analysis was performed. Heterogeneity was assessed with I squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
14
0
2
Order By: Relevance
“…It would be reasonable to assume that CDT might be associated with improved outcomes and less bleeding risk but this remains to be answered in the future. 67 Duration of anticoagulation therapy after PE/VTE confirmation in COVID-19 patients is usually three months of uninterrupted treatment with a direct oral anticoagulant as the drug of choice. However, this is right now based on the guidelines for patients with provoked DVT/PE and there are no data comparing a 3month vs a higher duration protocol.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be reasonable to assume that CDT might be associated with improved outcomes and less bleeding risk but this remains to be answered in the future. 67 Duration of anticoagulation therapy after PE/VTE confirmation in COVID-19 patients is usually three months of uninterrupted treatment with a direct oral anticoagulant as the drug of choice. However, this is right now based on the guidelines for patients with provoked DVT/PE and there are no data comparing a 3month vs a higher duration protocol.…”
Section: Managementmentioning
confidence: 99%
“…It would be reasonable to assume that CDT might be associated with improved outcomes and less bleeding risk but this remains to be answered in the future. 67…”
Section: Managementmentioning
confidence: 99%
“…Meta-analysis data have demonstrated that the incidence of PTS is lower following CDT in comparison to oral anticoagulation (odds ratio [OR]: 0.32; 95% confidence interval [CI]: 0.12-0.85, p = 0.022) [ 17 ]. This is further supplemented by guidance from the American College of Chest Physicians, American Heart Association, and the Society of Interventional Radiology who recommend CDT as an adjunct to anticoagulation rather than a standalone therapy [ 18 ], particularly in younger patients without major comorbidities and a long life-expectancy [ 12 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to treat MTS quickly could lead to post-thrombotic syndrome (PTS), which is thought to occur as a result of valvular incompetence and venous hypertension and leads to leg swelling and chronic skin changes such as hyperpigmentation, induration, and ulceration [5]. Meta-analysis has demonstrated the superiority of catheter-directed thrombolysis when compared to anticoagulation alone for the prevention and treatment of PTS [6].…”
Section: Discussionmentioning
confidence: 99%